Sensitivity analysis of a new approach to photovoltaic parameters extraction based on the total least squares method - Mesbahi, Oumaima (2022)
The degradation of photovoltaic modules and their subsequent loss of performance has a serious impact on the total energy generation potential. The lack of real-time information on the output power leads to additional losses since the panels may not be operating at their optimal point. To understand the behaviour, numerically simulate the characteristics and identify the optimal operating point of a photovoltaic cell, the parameters of an equivalent electrical circuit must first be identified. The aim of this work is to develop a total least-squares based algorithm which can identify those parameters from the output voltage and current measurements, taking into consideration the uncertainties on both measured quantities. This work presents a comparative study of the Ordinary Least Squares (OLS) and Total Least Squares (TLS) approaches to the estimation of the parameters of a photovoltaic cell.